INTEGRATION OF TRANSACTIONAL LEADERSHIP AND TEAMWORK IN IMPROVING EMPLOYEE PERFORMANCE: A STUDY AT BAZNAS EAST LOMBOK REGENCY - Jayadi, Hapipi; Safari, Agus (Politea : Jurnal Politik Islam, 2025)
This study aims to analyze the influence of transactional leadership and teamwork on employee performance at the National Amil Zakat Agency (BAZNAS) of East Lombok Regency. Using a descriptive qualitative approach, data was obtained through in-depth interviews, observations, and documentation of internal BAZNAS parties related to human resource management and institutional performance. The results show that the transactional leadership style applied through the reward system and discipline has contributed to the formation of a directed and productive work culture. On the other hand, structured and communicative teamwork also creates synergy between employees and strengthens the effectiveness of the institution's program implementation. These two variables, both partially and simultaneously, have been proven to have a positive impact on employee performance in terms of discipline, speed of service, and work responsibility. These findings confirm that the combination of assertive and managerial leadership with solid teamwork is an important prerequisite for building an effective and accountable social service organization. This research is expected to be a reference in the development of human resource management strategies in the zakat sector and other social institutions